INVESTIGATING THE USE OF COMPUTER IN TEACHING LEARNING ENGLISH - Alfin Amaliah Zahroh; Hepy Adityarini; Yeny Prastiwi (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
The way English is taught these days has advanced significantly with the usage of modern technology. The majority of English language instructors in the modern era actively use a variety of technical tools intended to provide the best possible instruction. One of the technical tool is “Computer”. This is one of the most important technological developments of our day, and because of its great performance efficiency and immense potential, which have decreased effort, time, and costs in many areas of use. The teaching and learning of languages is one of these. A computer is utilized for linguistic tasks that related to mastering the English skill. This essayaims to emphasize the advantages and applications of computers that can be used by the teacher in teaching learning English. Furthermore, it seeks to increase awareness of the advantages of computer technology in illuminating instruction for both educators and students. The design of this study is qualitative library method. Even though there are many shortcomings using computer, this can still help teachers in English teaching learning process and increase students’ motivation in learning English.